2019
DOI: 10.1093/cid/ciz456
|View full text |Cite
|
Sign up to set email alerts
|

Declines in Pneumonia and Meningitis Hospitalizations in Children Under 5 Years of Age After Introduction of 10-Valent Pneumococcal Conjugate Vaccine in Zambia, 2010–2016

Abstract: Background Pneumococcus is a leading cause of pneumonia and meningitis. Zambia introduced a 10-valent pneumococcal conjugate vaccine (PCV10) in July 2013 using a 3-dose primary series at ages 6, 10, and 14 weeks with no booster. We evaluated the impact of PCV10 on meningitis and pneumonia hospitalizations. Methods Using hospitalization data from first-level care hospitals, available at the Ministry of Health, and from the lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
3
11
0
Order By: Relevance
“…The decline in the frequency of probable bacterial and confirmed meningitis cases after PCV10 introduction is notable. The reduction of probable bacterial meningitis cases is consistent with findings by Mpabalwani et al [ 8 ], who observed substantial decline in meningitis and pneumonia hospitalizations among children aged <5 years in the first 3 years after PCV10 introduction in Zambia.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The decline in the frequency of probable bacterial and confirmed meningitis cases after PCV10 introduction is notable. The reduction of probable bacterial meningitis cases is consistent with findings by Mpabalwani et al [ 8 ], who observed substantial decline in meningitis and pneumonia hospitalizations among children aged <5 years in the first 3 years after PCV10 introduction in Zambia.…”
Section: Discussionsupporting
confidence: 91%
“…Pneumococcal disease remains a public health concern because it is associated with long-term sequelae and high case-fatality rates (CFRs), which worsen by the rise in resistance to commonly used and affordable antibiotics such as penicillin [ 7 , 8 ]. An estimated 1.6 million children under 5 years of age die every year as a result of pneumococcal disease, the highest burden being in sub-Saharan African countries with high human immunodeficiency virus (HIV) prevalence [ 8 , 9 ]. More than 95 pneumococcal serotypes have been identified, based on differences in the antigenic characteristics of their capsular polysaccharides.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Two studies from Brazil and one from Zambia found that changes in all-cause pneumonia hospital admissions among children younger than 5 years varied between a 2% increase and 38% decrease following the introduction of PCV10. 16,18,19 Mortality reduced by 39% among children aged 2-23 months who were admitted to CWMH with all-cause pneumonia, bronchiolitis, and asthma. Few studies have Data are the ratio of observed to expected cases (95% CI).…”
Section: Discussionmentioning
confidence: 99%